A global review of joint operating agreement disputes. (6th August 2020) - Martin, Tim; Gilbert, John; Gusy, Martin
Abstract: The article identifies and analyses disputes that frequently arise from Joint Operating Agreements (JOAs) in the upstream oil and gas (O&G) business from around the globe. The topics discussed in this article are: a brief introduction to JOAs, their use in the O&G industry, and their key principles and provisions the development and use of model JOAs and Accounting Procedures; customary industry practice regarding JOAs O&G law regarding JOAs; a review of reported court judgments and international arbitral awards that dealt with JOA disputes; and an analysis of the trends in JOA disputes and lessons that can be drawn from those sources.